Impact of Norwood versus hybrid palliation on cardiac size and function in hypoplastic left heart syndrome. Issue 12 (23rd February 2016) - Grotenhuis, Heynric B; Ruijsink, Bram; Chetan, Devin; Dragulescu, Andreea; Friedberg, Mark K; Kotani, Yasuhiro; Caldarone, Christopher A; Honjo, Osami; Mertens, Luc L
Abstract : Objective: The hybrid approach for hypoplastic left heart syndrome (HLHS) could theoretically result in better preservation of right ventricular (RV) function then the Norwood procedure. The aim of this study was to compare echocardiographic indices of RV size and function in patients after Norwood and hybrid throughout all stages of palliation. Methods: 76 HLHS patients (42 Norwood, 34 hybrid) were retrospectively studied. Echocardiography was obtained before stage I, before and after stage II, and before and after Fontan. Median follow-up was 4.9 years (range 1.1–8.5). Results: Baseline characteristics before stage I were similar. Hybrid patients demonstrated a significant decrease in RV fractional area change (FAC) between baseline and pre-stage II (36±9% vs 27±6%; p<0.01); Norwood patients remained stable (32±10% vs 32±7%; p=0.21). At pre-stage II, moderate/severe tricuspid valve (TV) regurgitation was found in nine Norwood (33%) and four hybrid (18%) patients (p=0.19). After stage II, the difference in FAC became insignificant (29±7% vs 25±8%, p=0.08) and moderate/severe TV regurgitation (TR) was found in 13 Norwood (48%) and four hybrid patients (19%) (p=0.18). At pre-Fontan, RV FAC was similar after Norwood and hybrid (34±5% vs 33±6%, p=0.69), which remained unchanged after Fontan. After Fontan, one Norwood and one hybrid patient had moderate TR. RV and TV size were similar for both groups at each time point. Conclusions: Patients after Norwood and hybrid procedures had equivalent indices of RV size, and systolic and diastolic function throughout all stages of palliation. Small differences in individual RV and TV indices are likely to be explained by differences in physiology or surgical timing rather than by intrinsic differences in myocardial and valve function.